Brucella abortus modulates macrophage polarization and inflammatory response by targeting glutaminases through the NF-κB signaling pathway - Zhao, Tianyi; Zhang, Zedan; Li, Yitao; Sun, Zhihua; Liu, Liangbo; Deng, Xingmei; Guo, Jia; Zhu, Dexin; Cao, Shuzhu; Chai, Yingjin; Nikolaevna, Usevich Vera; Maratbek, Suleimenov; et al. (Frontiers in Immunology, 2023)
The mechanism of Brucella infection regulating macrophage phenotype has not been completely elucidated until now. This study aimed to determine the mechanism of Brucella abortus in the modulation of macrophage phenotype using RAW264.7 cells as a model. RT-qPCR, ELISA and flow cytometry were used to detect the inflammatory factor production and phenotype conversion associated with M1/M2 polarization of macrophages by Brucella abortus infection. Western blot and immunofluorescence were used to analyze the role of nuclear factor kappa B (NF-κB) signaling pathway in regulation of Brucella abortus-induced macrophage polarization. Chromatin immunoprecipitation sequencing (Chip‐seq), bioinformatics analysis and luciferase reporter assay were used to screen and validate NF-κB target genes associated with macrophage polarization and further verify its function. The results demonstrate that B. abortus induces a macrophage phenotypic switch and inflammatory response in a time-dependent manner. With the increase of infection time, B. abortus infection-induced M1-type increased first, peaked at 12 h, and then decreased, whereas the M2-type decreased first, trough at 12 h, and then increased. The trend of intracellular survival of B. abortus was consistent with that of M2 type. When NF-κB was inhibited, M1-type polarization was inhibited and M2-type was promoted, and the intracellular survival of B. abortus increased significantly. Chip‐seq and luciferase reporter assay results showed that NF-κB binds to the glutaminase gene (Gls). Gls expression was down-regulated when NF-κB was inhibited. Furthermore, when Gls was inhibited, M1-type polarization was inhibited and M2-type was promoted, the intracellular survival of B. abortus increased significantly. Our data further suggest that NF-κB and its key target gene Gls play an important role in controlling macrophage phenotypic transformation. Taken together, our study demonstrates that B. abortus infection can induce dynamic transformation of M1/M2 phenotype in macrophages. Highlighting NF-κB as a central pathway that regulates M1/ M2 phenotypic transition. This is the first to elucidate the molecular mechanism of B. abortus regulation of macrophage phenotype switch and inflammatory response by regulating the key gene Gls, which is regulated by the transcription factor NF-κB.